Marine technology and sustainable development : green innovations - Olanrewaju, Oladokun Sulaiman (Advances in environmental engineering and green technologies (AEEGT) book series, 2014)
"This book examines theoretical frameworks and empirical research in the maritime industry, evaluating new technologies, methodologies, and practices against a backdrop of sustainability"--